The response threshold of Salmonella PilZ domain proteins is determined by their binding affinities for c-di-GMP - Pultz, Ingrid Swanson (Mol Microbiol, 2012)
c-di-GMP is a bacterial second messenger that is enzymatically synthesized and degraded in response to environmental signals. Cellular processes are affected when c-di-GMP binds to receptors which include proteins containing the PilZ domain. Although each c-di-GMP synthesis or degradation enzyme metabolizes the same molecule, many of these enzymes can be linked to specific downstream processes. Here we present evidence that c-di-GMP signaling specificity is achieved through differences in affinities of receptor macromolecules. We show that the PilZ domain proteins of Salmonella Typhimurium, YcgR and BcsA, demonstrate a 43-fold difference in their affinity for c-di-GMP. Modulation of the affinities of these proteins altered their activities in a predictable manner in vivo. Inactivation of yhjH, which encodes a predicted c-di-GMP degrading enzyme, increased the fraction of the population that demonstrated c-di-GMP levels high enough to bind to the higher-affinity YcgR protein and inhibit motility, but not high enough to bind to the lower-affinity BcsA protein and stimulate cellulose production. Finally, seven PilZ domain proteins of Pseudomonas aeruginosa demonstrated a 145-fold difference in binding affinities, suggesting that regulation of c-di-GMP signaling by binding affinity may be a conserved mechanism that allows organisms with many c-di-GMP-binding macromolecules to rapidly integrate multiple environmental signals into one output.